Hispathology Overview Uterus of the Mice (Mus musculus) ICR Female after Giving Extract of Papaya Seed (Carica papaya) - zulkarnain, Zulkarnain; Putri, Nur Maghfirah Qadriati; Sijid, St. Aisyah (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2023)
The high maternal mortality rate (MMR) and infant mortality rate (IMR) are the main cases in the health sector. Efforts to prevent this are encouraged to utilize plants that contain antifertility compounds, for example with papaya seeds (Carica papaya) which are able to minimize the side effects of contraceptive use. This study aims to determine the description of uterine histopathology of female ICR mice (Mus musculus) after administration of papaya seed extract (Carica papaya). The stages are determining the dose of papaya seed extract (Carica papaya), making papaya seed extract (Carica papaya), preparation and treatment of experimental animals, as well as making and reading uterine histopathology preparations of mice. The results showed that the administration of papaya seed extract (Carica papaya) for 34 days orally at a dose of 0.5 ml/bb was able to disrupt reproductive cells in mice (Mus musculus) characterized by abnormal endometrial thickening along with the amount of dose given.